2017
DOI: 10.1111/acer.13527
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Alcohol Withdrawal on Gut Permeability and Microbial Translocation in Patients with Alcohol Use Disorder

Abstract: Before alcohol withdrawal, MT markers were higher in patients with AUD than in HC. After 6 weeks of abstinence, an improvement in MT markers was observed. Our data suggest that there is a link between MT, its improvement, BMI, and cannabis consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 46 publications
1
32
1
Order By: Relevance
“…Ten studies reported a statistically significant association between 12 anthropometric measurements and IP . The correlation between BMI and IP ranged from a weak to moderate positive correlation, of which most were reported to have a weak positive correlation (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ten studies reported a statistically significant association between 12 anthropometric measurements and IP . The correlation between BMI and IP ranged from a weak to moderate positive correlation, of which most were reported to have a weak positive correlation (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The correlation between BMI and IP ranged from a weak to moderate positive correlation, of which most were reported to have a weak positive correlation (Table ). Two studies report BMI as an independent risk factor for altered IP as measured by zonulin levels ( β = 0.26; ±0.10; P < 0.05, β = 1.507; 0.34 SEM; P < 0.01) (Table ). Furthermore, it was reported in the general population that a BMI of >25.0 and BMI of >30.0 were associated with altered IP OR = 4.10 (95% CI: 1.87, 8.97; P < 0.001) and OR = 4.90 (95% CI: 1.49, 31.65; P = 0.047), respectively as measured by zonulin (>64 ng/mL) (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations